Cucurbitacin E inhibits cellular proliferation and induces apoptosis in melanoma by suppressing HSDL2 expression - Wen-Bei Liu; He-Li Wang; Lei Chen; Biao Tang; Guolin Ke; Shuai Wang; Yin-Qiao Sun; Junting Ma; Da-Lun Lyu (Chinese Medicine, 2022)
Abstract Background Melanoma is among the most aggressive types of skin malignancy and can have an unpredictable clinical course. Exploration of novel therapeutic targets and their regulators remains essential for the prevention and treatment of melanoma. Methods HSDL2 protein levels were examined by immunohistochemistry. The roles of HSDL2 in cell proliferation and apoptosis were identified by CCK-8 and colony formation assays. The function of HSDL2 in cell apoptosis was analysed by flow cytometry. Western blotting, cell proliferation and apoptosis and a xenograft tumour model were utilized to explore the inhibitory functions and mechanisms of CuE in melanoma. Results HSDL2 is overexpressed in melanoma and promotes melanoma progression by activating the ERK and AKT pathways. CuE could inhibit the ERK and AKT pathways by decreasing HSDL2 expression; therefore, CuE could inhibit melanoma growth in vitro and in vivo. Conclusion HSDL2 may be a promising therapeutic target against melanoma, and CuE can inhibit melanoma by downregulating HSDL2 expression.